2015
DOI: 10.1590/s1984-29612015070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Eimeria infections in sheep raised extensively in a semiarid region of Brazil

Abstract: The aim of this study was to identify and determine the prevalence of Eimeria species affecting sheep raised extensively in a semiarid region of Brazil. Fecal samples of native sheep were collected during the rainy and dry seasons. The degree of infection was determined by counting oocysts per gram (OPG) of feces, and the morphometric method was used for species identification. Oocysts were found in all the properties assessed, in which 68.3% of the animals were infected. The prevalence of oocysts was influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…The results obtained in this research showed that the Eimeria species has a wide distribution in the study area. Brazilian and worldwide studies have found a variable prevalence of Eimeria species in sheep; however, in the majority of cases, young animals had higher rates of positivity for the parasite (Lopes et al 2013, Souza et al 2015, Carrau et al 2018. The high prevalence of positive samples found in the present study (85.98%) probably occurred due to the focus on young lambs, the age group most susceptible to coccidiosis.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The results obtained in this research showed that the Eimeria species has a wide distribution in the study area. Brazilian and worldwide studies have found a variable prevalence of Eimeria species in sheep; however, in the majority of cases, young animals had higher rates of positivity for the parasite (Lopes et al 2013, Souza et al 2015, Carrau et al 2018. The high prevalence of positive samples found in the present study (85.98%) probably occurred due to the focus on young lambs, the age group most susceptible to coccidiosis.…”
Section: Discussioncontrasting
confidence: 50%
“…E. ahsata, E. bakuensis, E. granulosa, E. faurei, E. parva, E. pallida, and E. punctata are considered nonpathogenic but can cause impairment of growth due to nutrient malabsorption (Keeton & Navarre 2017, Taylor et al 2017, which might trigger subclinical coccidiosis in animals. Investigations carried out in different regions of Brazil already describe the presence of these species infecting sheep with variable prevalence (Tembue et al 2009, Silva et al 2011, Lopes et al 2013, Souza et al 2015, Macedo et al 2019 Previously studies demonstrated that the intensive and semi-intensive farming systems could facilitate the dissemination of Eimeria species (Lopes et al 2013, Tomczuk et al 2015. In this study, there were statistical differences (p=0.028) between animal infection and different breeding systems.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Those results can also be due to the production system because infection intensity of oocysts is influenced by two factors: intensity of animal production and the coccidiosis carrier-state in dams, which are the main source of infection to young (Cai & Bai., 2009). If animals are in a higher density, feces-urine fouled forage, sheep raised in confinement and semi-confinement conditions could be more heavily infected with coccidia than those grazing on pastures (Souza et al, 2015). In further studies is important to take into account the grazing conditions of the animals because it could be a risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…Around the world, the reported gastrointestinal nematodes affecting sheep and goats include: Haemonchus, Trichostrongylus, Teladorsagia/Ostertagia, Strongyloides, Bunostomum, Nematodirus, Chabertia, Trichuris, Cooperia, Skrjabinema and Oesophagostomum, and the general prevalence estimate is 75.8% (Asmare et al, 2016).On the other hand, the main species of coccidia in sheep are Eimeria ovinoidalis, E. crandallis, E. ahsata and E. parva in sheep (Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%